Answer:
(b)
has root 5 of multiplicity 2 and root -2 with multiplicity 1.
Explanation:
Here, the given expression is:
![(x-5)^2(x+2) = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/gsdlguo63w5712kmzer6dbsi9uz37e9hkp.png)
Now, here as we can see from the given expression,
It has 2 roots.
![(x-5)^2(x+2) = 0 \implies (x-5)(x-5)(x+2) = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/h5swuf4iri2im7ol4cagmp7r4yx4vgr5ga.png)
⇒ Either ( x- 5) = 0, or ( x + 2) = 0
⇒ either x = 5 or x = -2
So, x =5 and x = -2 are the ONLY TWO ROOTS of the given expression.
Now, 5 is a root of multiplicity 2 as
![(x-5)^2 = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/rw94hwenv8qvprpz5piffdrrsdr0cp3iox.png)
and, -2 is a root of multiplicity 1 as ( x + 2) = 0
Hence,
has root 5 of multiplicity 2 and root -2 with multiplicity 1.